Study on Blending of Wall Material of the Nonel Tube by CSW/PE-g-MAH. (23rd December 2019) - Li, Hong-wei; Zhang, Bin-bin; Yang, Ji-nian; Li, Huan; Gui, Ji-chang; Lei, Zhan
Abstract : In order to improve the strength and resistance of ordinary nonel tubes, calcium sulfate whiskers (CSW, treated with silane coupling agent) and maleic anhydride grafted polyethylene (PE-g-MAH) are used to control the wall material of the nonel tube that the blending of the low-density polyethylene was enhanced. The effects of mass fraction of CSW or PE-g-MAH on the tensile properties, interfacial structure, melting and crystallization characteristics, and thermal decomposition behavior of the composite system were studied, and the thermal decomposition kinetics were calculated. The results show that, relative to pure LDPE, the strength of LDPE/CSW (85/15) is increased by 7.58%, and the strength of LDPE/CSW/PE-g-MAH (84/15/1) is increased by 7.58%. The addition of CSW or PE-g-MAH has gradually changed the fracture mode of the LDPE matrix. Thermal analysis shows that CSW can reduce the crystallinity of LDPE. The melting and crystallization characteristics of LDPE/CSW/PE-g-MAH composites have little effect, but the thermal decomposition stability is improved. The kinetic analysis showed that the reaction order ( n ) was around 1, CSW could improve LDPE/CSW thermal decomposition activation energy, and PE-g-MAH increased the thermal decomposition activation energy of LDPE/CSW/PE-g-MAH.